International Capacity Building for Sustainable Growth: What Role for the World’s Learned Societies? - Elizabeth Bell (Foresight and STI Governance)
The problem of Learned Societies’ contribution in the international capacity building process and the engagement of societies from developing countries into it arises much concern nowadays. Thus the overview of contemporary UK Learned Societies’ initiatives aimed at strengthening scientists’ role in this process was recently made in the UK. It embraces historical background of informal scientific networks’ emergence and their participation in the S&T development on the national and global levels. The author therefore proposes a number of steps that should help to build strong relationships between Learned Societies and various funding bodies including governments.